Kleurengrafiek en Bronssculptuur. - Juwet, Willy; Roesems-Asselman, Lieve; Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1986)
Alechinsky, Pierre ; Baeyens, Martin R. ; Bilquin, Jean ; Bolle, Jos ; Bosschem, Willy ; Dacos, Guy ; Frimout, Cyr ; Goezu, André ; Hoorne, Emiel ; Ivens, Renaat ; Landuyt, Octave ; Guy Leclercq ; Maieu, Frank ; Mara, Pol ; Minnaert, Frans ; Piron, Luc ; Raveel, Roger ; Szymkowicz, Charles ; µVinche, Lionel ; Vlerick, Pierre ; Wisniewski, Andrzej K. ; Minnebo, Hubert ; Monteyne, Roland ; Spilliaert, Pol ; Strebelle, Olivier ; Van Gysegem, Paul
Kleurengrafiek en Bronssculptuur, Hof ter Nederloo, Sint-Pieters-Leeuw, 1 mei - 22 juni 1986
boek